KEPEMIMPINAN DEMOKRATIS (Studi kasus Kepemimpinan Pada PT Acryl Textile Mills) : KEPEMIMPINAN DEMOKRATIS (Studi kasus Kepemimpinan Pada PT Acryl Textile Mills) - Utami, Pri (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2025)
The success or failure of organizational goals depends on the leader. Therefore, leadership that is able to move and manage the company well is needed. In short, a leader is the driving force of the life of the company or organization he manages.The type of leadership used by PT Acryl Textile Mills is democratic, as shown by the director who is happy to accept criticism, suggestions, and opinions of others. At PT Acryl Textile Mills, the leader's policy shows that the leader feels that subordinates are very important in helping his duties. This is shown by holding meetings with subordinates and accepting criticism, suggestions, and opinions.